2017
DOI: 10.1002/pc.24435
|View full text |Cite
|
Sign up to set email alerts
|

Chemical treatment of cotton stalk and its effects on mechanical, rheological and morphological properties of Polypropylene/cotton stalk bio‐composites

Abstract: Cotton stalk as commercially viable bio fiber for preparing bio‐composites is explored of late, and the effects of various chemical treatments of cotton stalk fiber on mechanical, rheological and morphological properties of Polypropylene (PP)‐Cotton stalk (CS) bio‐composites are reported in this study. PP‐CS bio‐composites were prepared by varying the amount of cotton stalk from 10 to 50% by melt mixing in twin screw extruder and then injection molded to make specimen. PP‐CS bio‐composites with 50 wt% untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Generally, glass, para-aramid, carbon, polyethylene, ceramic, and natural fibers are used as reinforcement. 16,27,[29][30][31][32][33][34][35] Among the various fibers, glass and carbon fibers are most commonly used due to their freedom to use either thermoset or thermoplastic matrix. 29 The imperative characteristics of glass fibers include their low cost, high strength and modulus, high chemical resistance, good heat resistance, and excellent insulating properties.…”
Section: Glass Fiber-reinforced Epoxy Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, glass, para-aramid, carbon, polyethylene, ceramic, and natural fibers are used as reinforcement. 16,27,[29][30][31][32][33][34][35] Among the various fibers, glass and carbon fibers are most commonly used due to their freedom to use either thermoset or thermoplastic matrix. 29 The imperative characteristics of glass fibers include their low cost, high strength and modulus, high chemical resistance, good heat resistance, and excellent insulating properties.…”
Section: Glass Fiber-reinforced Epoxy Nanocompositesmentioning
confidence: 99%
“…Fiber‐reinforced polymer composites comprise a polymer matrix with high‐strength fiber(s) as reinforcement. Generally, glass, para‐aramid, carbon, polyethylene, ceramic, and natural fibers are used as reinforcement 16,27,29–35 . Among the various fibers, glass and carbon fibers are most commonly used due to their freedom to use either thermoset or thermoplastic matrix 29 .…”
Section: Glass Fiber‐reinforced Epoxy Nanocompositesmentioning
confidence: 99%
“…Moreover, it is reported that the cellulose fibers from cotton stalks have higher mechanical properties than those from most lignocellulosic byproducts. Many studies show that alkali treatment removes amorphous materials such as hemicellulose, lignin, and pectin from the surface of cellulose fiber bundles and develops interfacial bonding between fiber and matrix which provide better mechanical properties (Hou et al, 2014;Reddy and Yang, 2009;Sachan et al, 2017;Zhou et al, 2017;Li et al, 2016). In addition, it has been observed that with the increase in temperature, the amount of cellulose also increased.…”
Section: Thermal Assisted Alkaline Pretreatmentmentioning
confidence: 99%
“…Examples include flax [ 15 , 16 ], jute [ 17 , 18 ], corn stalks [ 19 ], eucalyptus fibers [ 20 ], coconut shell fibers [ 21 , 22 ], and cotton stalk fibers [ 23 ]. Among these, cotton stalk fibers (CSFs), derived from the agricultural waste of the globally significant economic crop cotton, hold immense potential for development and utilization [ 23 , 24 , 25 ]. From a chemical composition perspective, CSFs, as lignocellulosic biomass, primarily consist of cellulose, hemicellulose, and lignin [ 25 ].…”
Section: Introductionmentioning
confidence: 99%